2011
DOI: 10.1063/1.3603015
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric function and optical properties of quaternary AlInGaN alloys

Abstract: The optical properties of quaternary AlxInyGa1-x-yN alloy films with 0.16<x<0.64 and 0.02<y<0.13 are presented. The (0001)-oriented AlInGaN layers were grown by metal-organic vapor phase epitaxy on thick GaN/sapphire templates. High-resolution x-ray diffraction measurements revealed the pseudomorphic growth of the AlInGaN films on the GaN buffer. Rutherford backscattering and wavelength-dispersive x-ray spectroscopy analysis were used in order to determine the composition of the all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…We use k Á p formalism [11] and employ the same parameters as provided in Ref. [6]. The in-plane strain is evaluated from the XRD measurements by using the expression e xx ¼ ða À a ) for the SB samples should be noticed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use k Á p formalism [11] and employ the same parameters as provided in Ref. [6]. The in-plane strain is evaluated from the XRD measurements by using the expression e xx ¼ ða À a ) for the SB samples should be noticed.…”
Section: Resultsmentioning
confidence: 99%
“…The band-gap values for Ga-rich InGaN samples were obtained by fitting the experimental DF with the parametric oscillator model presented in Refs. [5,6].…”
mentioning
confidence: 98%
“…1, is plotted as a function of the nominal lattice constant a, calculated by Vegard's law. Here, the bowing parameters are updated by the latest results from the literature: The bowing parameters used here are 0.9 eV for AlGaN, 17 1.65 eV for InGaN, 17 and a quite high and constant value of 5.2 eV for AlInN. 11,18 The bowing parameter for AlInN is still vague and might also be In dependent, especially for the In-rich region.…”
Section: Resultsmentioning
confidence: 99%
“…11,18 The bowing parameter for AlInN is still vague and might also be In dependent, especially for the In-rich region. 17 The contour lines in the quaternary area illustrate the total polarization of quaternary barriers for the corresponding barrier composition, being pseudomorphically grown on a GaN buffer. The thicker red line indicates polarization matching to GaN.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that growth of high crystalline quality AlInGaN layers is difficult [12], though such issues do not appear to be fundamental. Recently, Sakalauskas et al have grown a wide range of AlInGaN materials on c-place sapphire substrates with GaN templates [13] and studied their optical properties. They confirmed pseudomorphic growth of AlInGaN films by high-resolution x-ray diffraction measurements.…”
Section: Polarization Charge Matched Duv Ld Designmentioning
confidence: 99%